Contrastive Analysis of The Meanings of Japanese and Indonesian Kanyouku Using Body Names - Elfa Regita Utami; Felicia Aprilani (Universitas WIdyatama, 2022)
Idioms are figurative utterances often found in everyday life. Idioms apply the names of body parts in humans as forming lexical elements. Idioms in Japanese are called kanyouku. Japanese and Indonesian idioms, although they have the same meaning in common, yet the idioms of these two languages have differences. When comparing Indonesian and Japanese idioms, you will find similarities and differences, both in terms of lexical meaning, idiomatic meaning, and the constituent elements of the two idiom languages. The author obtained data from Japanese kanyouku videos, Indonesian phrasebooks, and social media Instagram. The data were collected by means of the listening method using note-taking techniques, then the data were analyzed by the meaning and structure. The authors used the referential method using the specific element sorting technique. Based on what the author had analyzed, there were 15 data kanyouku applied the names of body parts, 6 data that had the same meaning and words used, and 9 kanyouku data that had different words but propertied the same meaning as Indonesian idioms.